2020
DOI: 10.31506/jsc.v1i2.7806
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Komunikasi Perwakilan BKKBN Provinsi Banten Dalam Pengendalian Penduduk di Provinsi Banten

Abstract: The background of this research is that the population in Banten Province ranks 5th most populous in Indonesia reaching 12,203,148 people with the 3rd fastest population growth rate in Indonesia reaching 2.07% during 2015-2016. The progress of human development in Banten in 2017 experienced a slowdown marked by the growth of HDI (Human Development Index) which reached 0.65%, lower than the growth in 2016 which reached 0.98%. HDI is an important indicator to measure success in an effort to build quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…16 Tahun 2019 telah mengatur bahwa pernikahan hanya diizinkan pada pasangan laki-laki dan perempuan yang telah mencapai usia 19 tahun. Sedangkan Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) merekomendasikan usia minimal menikah bagi wanita adalah 21 tahun dan pria 25 tahun (Natalia, 2016). Pembatasan usia tersebut bukannya tidak beralasan, melainkan untuk menjamin kesehatan ibu dan anak serta menjaga kualitas dari generasi penerus bangsa.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…16 Tahun 2019 telah mengatur bahwa pernikahan hanya diizinkan pada pasangan laki-laki dan perempuan yang telah mencapai usia 19 tahun. Sedangkan Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) merekomendasikan usia minimal menikah bagi wanita adalah 21 tahun dan pria 25 tahun (Natalia, 2016). Pembatasan usia tersebut bukannya tidak beralasan, melainkan untuk menjamin kesehatan ibu dan anak serta menjaga kualitas dari generasi penerus bangsa.…”
Section: Pendahuluanunclassified
“…Program PUP merupakan upaya untuk memberikan pengertian dan meningkatkan kesadaran kepada remaja akan pentingnya mempersiapkan berbagai aspek dalam merencanakan keluarga, yaitu aspek kesehatan, ekonomi, psikologi, dan agama. Tujuan dari PUP adalah meningkatkan usia perkawinan hingga batas minimal, yang diharapkan dapat menurunkan jumlah anak yang dilahirkan dari pernikahan dini (Natalia, 2016).…”
Section: Pendahuluanunclassified
“…SLR has also demonstrated that the planning for communication strategies for family planning programs developed by BKKBN representatives in various provinces is a genuine effort to demonstrate Regional Institutions' seriousness in disseminating information to reduce birth rates and control the population. Research conducted by Ernayanti, Mukhroman, and Muldi [28] revealed that population control programs must reach all areas in Indonesia, both urban and rural. Although the methods and conditions in the field differ, everyone must receive the same information tailored to their own needs.…”
Section: E Contextmentioning
confidence: 99%